Effect of ice gel compress towards labor pain during Active Phase Stage I at private midwivery clinics in Surabaya City area - Nova Elok Mardliyana; Abkar Raden; Umu Hani EN (Universitas Airlangga, 2017)
Objectives: to clarify the effect of gel ice pack against the first stage of labor pain of the active phase.Materials and Methods: The study design True experiment with design Randomized Controlled Trial conducted in several places independently practicing midwives. Research samples were 44 maternal maternity which 22 were given ice gel packs and 22 maternal performed relaxation techniques. The analysis includes statistical chi-square test with 95% confidence interval.Results: The results showed no significant correlation between the administration of gel ice packs to decrease pain intensity active phase of the first stage of labor with p value of 0.000 and a confidence interval: 2.1 to 18.3.Conclusion: Mother maternity given gel ice packs experienced lower pain than those not given the gel ice pack.